Bio-orthogonal Metabolic Fluorine Labeling Enables Deep-Tissue Visualization of Tumor Cells In Vivo by 19 F Magnetic Resonance Imaging - Chen, Dongxia; Lin, Yaying; Li, Ao; Luo, Xiangjie; Yang, Chaoyong; Gao, Jinhao; Lin, Hongyu (Analytical chemistry (Washington), 2022)
The high resolution, deep penetration, and negligible biological background of F magnetic resonance imaging (MRI) makes it a potential means for imaging various biological targets in vivo. However, the limited targeting strategies of current F MRI probes significantly restrict their applications for in vivo tracking of low-abundance targets and specific biological processes, which greatly stimulates the investigations on new targeting methods for F MRI. Herein, we report a strategy, termed as bio-orthogonal metabolic fluorine labeling, for selective cellular F labeling, which permits in vivo imaging of tumor cells with high specificity. This strategy exploits the display of azido groups on the cell surface via selective uptake and metabolic engineering of tetra-acetylated -azidoacetylmannosamine (Ac ManAz) by cancer cells and subsequent rapid and specific bio-orthogonal ligation between azido and cyclootynyl groups to incorporate F-containing moieties on the surface of cancer cells. We validated the feasibility of this method on the cellular level with A549 and HepG2 cells and further illustrated the application of this method for in vivo deep-tissue visualization of cancer cells with A549 tumor-bearing BALB/c mice using hot spot F MRI. Our strategy expands the arsenal for targeted F MRI and provides a promising method for imaging biological targets in living subjects with high tissue penetration and low biological background.